Analisis Efisiensi Propeler Dengan Desain Bilah Melingkar - Anugerah Putra, Bima; Ashfi Rayhan, Fajri (Fakultas Teknik UPN Veteran Jakarta, 2024)
The toroidal propeller, characterized by its circular blade shape, has gained attention for its potential benefits, including increased efficiency and reduced noise levels. Despite its advantages, limited scientific literature exists on toroidal propeller research, predominantly relying on field experiments. This study seeks to assess the toroidal propeller's performance by comparing it to a conventionally shaped propeller with similar geometric parameters. Parameters such as propeller diameter, number of blades, hub diameter, and blade front view are adjusted in the conventional propeller model to mimic the toroidal design. The pitch parameter of the conventional propeller is varied to explore its ability to match the efficiency of the toroidal propeller. Utilizing Computational Fluid Dynamics (CFD) simulations through Simscale software, propeller models are evaluated across a range of RPM (1000 - 6000). The simulations yield thrust and torque values, subsequently used to calculate efficiency. Results indicate that thrust and torque increase with higher pitch and RPM. Interestingly, a variation of the conventional propeller with a pitch of 171.45 mm demonstrates superior efficiency compared to the toroidal propeller, albeit with lower thrust. Visualization of fluid flow on each model reveals optimal flow in the toroidal propeller, devoid of vorticity. This study enhances understanding of toroidal propellers, offering insights that contribute to the ongoing development of this technology.